Evidence of exposure to Rickettsia felis in Australian patients - Yen Thon Teoh; Sze Fui Hii; Stephen Graves; Robert Rees; John Stenos; Rebecca J. Traub (One Health, 2016)
Rickettsia felis is an emerging zoonosis, causing flea-borne spotted fever (FBSF). Serological diagnosis is typically confounded by cross-reactivity with typhus group rickettsiae and prior to the development of specific serological methods, cases of FBSF in Australia were misdiagnosed. Patient sera tested between August 2010 and December 2013 and known to be seropositive to R. typhi by immunofluorescence antibody testing (IFAT) were subsequently retested against R. felis using an R. felis-specific IFAT. Sera of 49 patients were of a sufficient quality to be included in re-analysis. A classification of FBSF and murine typhus (MT) was attributed to fourteen and seven patients respectively, based on a minimum four-fold higher antibody titre to R. felis than to R. typhi and vice versa. Twenty-eight patients were classified as indeterminate for either R. felis or R. typhi (antibody titres within two-fold of one another). Historically, it is likely that Australian patients clinically ill with FBSF were misdiagnosed. It is important that medical practitioners consider FBSF as part of their differential diagnoses, and obtain relevant history with regard to patient's exposure to domestic pets and their fleas. Australian microbiology diagnostic laboratories should include serological testing for R. felis as part of the diagnostic panel for febrile diseases. Veterinarians are encouraged to increase their awareness of this emerging zoonosis and advocate flea control in pets.